ANALISIS VARIASI BAHASA PADA SHORT MOVIE RIZKY FEBIAN JEJAK BIAN - Anfiya'ul Baroroh; Arti Prihatini (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2024)
The variety of languages used by the characters in Rizky Febian's short film "Jejak Bian" is very much, so it is interesting and needs to be studied. This study aims to identify and describe the types of language variations and the factors that cause language variations in Rizky Febian's Short Movie "Jejak Bian". Qualitative descriptive is a type of research and research method used by researchers to analyze this short film. While the sociolinguistic approach is an approach used by researchers as a point of view when analyzing, with the theory proposed by Chaer & Agustin. The source of data in this study is in the form of dialogue between characters contained in Rizky Febian's Short Movie "Jejak Bian". The instrument used in this study, namely by making observations. While the technique of observation, recording, and note-taking, used by researchers in collecting data that has been found. The results found, namely: (A) language variations in terms of speakers, namely 1) dialect, consisting of (a) native Jakarta dialect, (b) Medan dialect, (c) Sundanese dialect, (d) Balinese dialect, and 2) sociolect. (B) Language variations in terms of formality, namely the variety of business, the variety of casual, the variety of familiarity. (C) Language variation in terms of facilities, namely the spoken variety. (D) The factors that cause language variations in Rizky Febian's Short Movie “Jejak Bian”, namely 1) the geographical and social background of the speaker and 2) the subject of the conversation.